Adaptation and validation of the research task distractor scale in Peruvian university students - Mamani-Benito, Oscar; Zurita, Jhoanna Marilú Llaguento; Vásquez, Olga Lidia García; Guerrero, Fiorella Sadith Castañeda; Morales-García, Wilter C.; Chaparro, Josué Turpo (Frontiers in Education, 2023)
Unconventional distractions such as electronic devices are stimuli that divert attention during study tasks, especially those related to scientific research exercises in undergraduate education. In the absence of precise instruments to measure this phenomenon, the objective was to adapt and validate the Scale of Distractions in Research Tasks among Peruvian university students. The study is classified as an instrumental cross-sectional design, involving 1003 university students aged between 18 and 47 years (M = 20.93, SD = 4.30) from three regions of Peru (Coast, Highlands, and Jungle), selected through convenience sampling. Content validity was assessed using Aiken's V coefficient, internal structure was examined through confirmatory factor analysis, and reliability was measured using the Omega coefficient. The results indicated that the judges positively evaluated the 5 items (V > .70), the internal structure confirmed the original model with satisfactory fit indices (χ^2 (2) = 5.47, p = .187, CFI = .998, RMSEA = .023, and SRMR = .010), and the reliability was acceptable (ω = .86). In conclusion, the Peruvian version of the Scale of Distractions in Research Tasks has demonstrated to be a valid and reliable instrument, characterized by its brevity and a unifactorial structure.